Influência ambiental na qualidade da água do Arroio Doze Passos, Ouro, SC - Seidel, Charles (2012)
Water is the main factor for the development and growth of communities, especially the rural ones. The objectives of this study were to evaluate the water quality and to determine the influence of natural and anthropogenic environmental factors on the water quality of Doze Passos stream. This study was conducted in the watershed Arroio Doze Passos in the Midwest region of Santa Catarina state, southern Brazil, with data obtained from November 2004 to October 2009. This watershed has an area of 17.78km², where intensive agriculture is developed (mainly corn and wheat) and livestock (mainly pigs, dairy cattle and poultry). It was observed that the stream water has low quality due the high values of total P, ortho P, turbidity, total coliform bacteria, and fecal coliforms. The water the Doze Passos stream is framed in Class 4 of the CONAMA classification. The main factor of poor water quality is the presence of organic-origin manure, which is caused by land use out of its fitness ability, coupled with inadequate management of waste, and lack of environmental planning. However, water quality, in general, increases from the stream's spring to its mouth. The reduction in the percentage of arable land and field, and in the number of domestic complexes along the stream, coupled with the increase of forest area with APP and preserved, added to the effect of aeration caused by the slope, explain the considerable capacity recovery of water quality as it approaches the stream mouth.